Numerical prediction of curing and process-induced distortion of composite structures - Bernath, Alexander (Karlsruhe KIT Scientific Publishing, 2021)
Fiber-reinforced materials offer a huge potential for lightweight design of load-bearing structures. However, high-volume production of such parts is still a challenge in terms of cost efficiency and competitiveness. Numerical process simulation can be used to analyze underlying mechanisms and to find a suitable process design. In this study, the curing process of the resin is investigated with regard to its influence on RTM mold filling and process-induced distortion.
English
Keywords: Mechanical engineering & materials; Prozesssimulation; Leichtbau; Faserverbundwerkstoff; Formfüllsimulation; Bauteilverzug; process simulation; lightweight design; composite; mold-filling simulation; process-induced distortion